Trends in 3D GIS Development - Zlatanova, Siyka; Abdul Rahman, Alias; Pilouk, Morakot (The Hong Kong Institution of Engineering Surveyors, 2002)
Currently, a variety of software is capable of handling a wide range of spatial problems, beginning with approaches for describing spatial objects to quite complex analysis and 3D visualisation. However, an increasing number of applications need more advanced tools for representing and analysing the 3D world. Among all types of systems dealing with spatial information, GIS has proven to be the most sophisticated system that operates with the largest scope of objects (spatial and semantic), relationships and provide means to analyse them. However, what is the status of 3D GIS? It is the aim of this paper to find the answer by analysing both available software and efforts of researchers. An overview of several software packages and 3D case studies performed in Oracle and Microstation is given to provide knowledge about the 3D functionality offered by commercial systems. The most significant achievements in the 3D research area concerning key issues of 3D GIS, i.e. 3D structuring and 3D topology are summarized to portray the current research status. At the end, some of the issues and problems involved in developing such a system are presented and recommendations on directions for further research are made. The scope of the paper is limited to 3D GIS systems and research in vector domain. Problems of subsurface applications are excluded as well.